Welfare implications of public education spending rules - Konstantinos Angelopoulos; Jim Malley; Apostolis Philippopoulos (Center for Economic Studies and ifo Institute (CESifo), 2008)
In this paper, we quantitatively assess the welfare implications of alternative public education spending rules. To this end, we employ a dynamic stochastic general equilibrium model in which human capital externalities and public education expenditures, financed by distorting taxes, enhance the productivity of private education choices. We allow public education spending, as share of output, to respond to various aggregate indicators in an attempt to minimize the market imperfection due to human capital externalities. We also expose the economy to varying degrees of uncertainty via changes in the variance of total factor productivity shocks. Our results indicate that, in the face of increasing aggregate uncertainty, active policy can significantly outperform passive policy (i.e. maintaining a constant public education to output ratio) but only when the policy instrument is successful in smoothing the growth rate of human capital.
Keywords: A00; E60; E62; 330; Education spending; growth; welfare; Öffentliche Bildungsausgaben; Bildungsinvestition; Externer Effekt; Steuer; Bildungsverhalten; Produktivität; Wohlfahrtseffekt; Theorie